2022
DOI: 10.1021/acs.est.1c08388
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Transformations of Diverse Dissolved Organic Matter Fractions with Sulfate Radicals

Abstract: Dissolved organic matter (DOM) scavenges sulfate radicals (SO4 •–), and SO4 •–-induced DOM transformations influence disinfection byproduct (DBP) formation when chlorination follows advanced oxidation processes (AOPs) used for pollutant destruction during water and wastewater treatment. Competition kinetics experiments and transient kinetics experiments were conducted in the presence of 19 DOM fractions. Second-order reaction rate constants for DOM reactions with SO4 •– (k DOM,SO4 •– ) ranged from (6.38 ± 0.53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 74 publications
(158 reference statements)
1
40
1
Order By: Relevance
“…In addition, the membrane flux restored by ∼20% in the presence of 1.0 M of TBA, revealing that even though both SO 4 · – and HO · contributed to the cleaning of EfOM fouling, the HO · played a more critical role in such a process. This is reasonable by considering the pH-dependent conversion of SO 4 · – to HO · (the R­()), and the larger reaction kinetics of HO · with EfOM (e.g., (0.27–1.21) × 10 9 M C –1 s –1 ) than that for SO 4 · – (e.g., 0.75 × 10 7 and 2.48 × 10 8 M C –1 s –1 ). , In addition, the influence of TBA on the cleaning efficacy of α-Al 2 O 3 @Mn 1.5 FeO 6.35 CM was also conducted under neutral pH conditions (as such, the transition of SO 4 · – to HO · can be retarded), which still resulted in negligible restoration of the membrane flux (Figure D), further highlighting the role of HO · .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, the membrane flux restored by ∼20% in the presence of 1.0 M of TBA, revealing that even though both SO 4 · – and HO · contributed to the cleaning of EfOM fouling, the HO · played a more critical role in such a process. This is reasonable by considering the pH-dependent conversion of SO 4 · – to HO · (the R­()), and the larger reaction kinetics of HO · with EfOM (e.g., (0.27–1.21) × 10 9 M C –1 s –1 ) than that for SO 4 · – (e.g., 0.75 × 10 7 and 2.48 × 10 8 M C –1 s –1 ). , In addition, the influence of TBA on the cleaning efficacy of α-Al 2 O 3 @Mn 1.5 FeO 6.35 CM was also conducted under neutral pH conditions (as such, the transition of SO 4 · – to HO · can be retarded), which still resulted in negligible restoration of the membrane flux (Figure D), further highlighting the role of HO · .…”
Section: Resultsmentioning
confidence: 69%
“…Based on the above results, the clean mechanism for the present α-Al 2 O 3 @Mn 1.5 FeO 6.35 CM by Oxone can be drawn as follows: Oxone (HSO 5 – ) is rapidly activated by the Mn 1.5 FeO 6.35 layer (i.e., Fe II , Mn II , and Mn III ) to generate SO 4 ·– ; meanwhile, an alkaline condition causes a transition from the SO 4 ·– -dominated to HO · -dominated oxidation process because of one-electron oxidation of OH – by SO 4 ·– (SO 4 · – + OH – → SO 4 2– + HO · , k = 6.5 × 10 7 M –1 s –1 ). , Additionally, the reaction kinetics of HO · with EfOM (e.g., (0.27–1.21) × 10 9 M C –1 s –1 ) are 1–2 order of magnitude larger than that of SO 4 ·– (e.g., 0.75 × 10 7 and 2.48 × 10 8 M C –1 s –1 ). , Therefore, the HO · displayed higher contributions to the EfOM fouling removal than that by SO 4 ·– under the given conditions. Besides, it is noticed that the membrane was operated in a cross-flow mode once the EfOM foulants detached from the membrane surface that can be further removed by the water flow.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The rates are similar to those obtained with SO 4 •– , CO 3 •– , and Cl 2 •– using DOM from different sources. They depend on the DOM’s TAC. ,, The selectivity of these reactive species (i.e., SO 4 •– , CO 3 •– , Cl 2 •– , and ADN­(-H) • ) toward different DOM structures may be responsible for the difference in the reaction rate constants. Like SO 4 •– , CO 3 •– , and Cl 2 •– , ADN­(-H) • may preferentially react with electron-rich moieties (e.g., phenols and thiols), but it may be resistant to react with electron-poor moieties (e.g., aliphatic structures and aromatics bearing electron-withdrawing groups). ,,, A previous study evaluating the quenching reactions of DMABN •+ by three DOM isolates found a similar trendthe rate constants of the quenching reactions increased with increasing electron-donating capacity of DOM …”
Section: Resultsmentioning
confidence: 99%
“…Figure a summarizes rate constant ranges between DOM and common RS. As the figure shows, k •OH,DOM ≈ k Cl•,DOM (10 8 –10 9 M C –1 s –1 ) > k Br•,DOM (10 7 –10 8 M C –1 s –1 ) > k SO 4 •–,DOM (10 7 –10 8 M C –1 s –1 ) > k Cl 2 •–,DOM (10 6 –10 7 M C –1 s –1 ) > k Br 2 •–,DOM (10 5 –10 6 M C –1 s –1 ) ≈ k CO 3 •–,DOM (10 5 –10 6 M C –1 s –1 ). ,,,, For example, the second-order reaction rate constant for Suwannee River fulvic acid (SRFA) reacting with • OH is (1.86 ± 0.25) × 10 8 M C –1 s –1 . With Cl • it is (4.12 ± 0.32) × 10 8 M C –1 s –1 , with Br • (3.0 ± 0.3) × 10 8 , with SO 4 •– (2.28 ± 0.07) × 10 7 , with Cl 2 •– (1.64 ± 0.35) × 10 7 , with CO 3 •– (1.74 ± 0.06) × 10 6 , and with Br 2 •– (9.4 ± 1.3) × 10 5 M C –1 s –1 .…”
Section: Antagonistic Influence Of Dom On Troc Removal In Aopsmentioning
confidence: 89%